ICRF heating of hydrogen plasmas with two mode conversion layers - Kazakov, Ye.O.; Van Eester, D.; Lerche, E.; Pavlenko, I.V.; Girka, I.O.; Weyssow, B. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
ICRF mode conversion heating regime is widely used in present-day tokamaks. The theoretically predicted mode conversion enhancement due to the constructive interference of the fast wave reflected from the evanescence layer with a wave reflected from the high-field side cutoff was first experimentally identified in JET in (3He)D experiments. This effect was recently tested in (3He)H plasmas, which is one of the ICRF heating scenarios considered for the non-activated phase of ITER operation. Due to the presence of the intrinsic D-like impurities in JET (e.g., C6+, 4He) the supplementary conversion layer was produced in the plasma that defined the interference conditions. The different behavior of the conversion efficiency observed at various 3He concentrations is analyzed in the paper on the basis of the theory of the fast wave mode conversion in plasmas with two evanescence layers. Высокочастотный нагрев плазмы в режиме конверсии мод широко используется в современных токамаках. Теоретически предсказанное увеличение эффективности конверсии вследствие интерференции быстрой волны, отраженной от области непрозрачности, с волной, отраженной от отсечки со стороны сильного магнитного поля, было впервые экспериментально подтверждено в (3He)D-экспериментах на токамаке JET. Данный эффект изучался в (3He)H-плазме, которая рассматривается как один из сценариев ВЧ-нагрева во время начальной стадии работы ITER. Вследствие присутствия в плазме JET дейтериеподобных примесей (C6+, 4He) образовывалась дополнительная область непрозрачности, которая определяла условия интерференции волн. Различное поведение коэффициента конверсии, наблюдаемое при разных значениях концентрации ионов 3He, анализируется в работе с помощью теории конверсии быстрых волн в плазме с двумя областями непрозрачности. Високочастотне нагрівання плазми в режимі конверсії мод широко застосовується в сучасних токамаках. Теоретично передбачене збільшення ефективності конверсії внаслідок інтерференції швидкої хвилі, що відбита від шару непрозорості, з хвилею, що відбита від відсічки з боку сильного магнітного поля, було вперше експериментально підтверджено в (3He)D-експериментах на токамаці JET. Цей ефект нещодавно апробовано в (3He)H-плазмі, яка розглядається як один із сценаріїв ВЧ-нагрівання на початковій стадії роботи ITER. Внаслідок присутності в плазмі JET дейтерієподібних домішок (C6+, 4He) утворювався додатковий шар непрозорості, що визначав умови інтерференції хвиль. Різна поведінка коефіцієнту конверсії, що спостерігалася за різної концентрації іонів 3He, аналізується в роботі на основі теорії конверсії швидких хвиль в плазмі з двома шарами непрозорості.